2000
DOI: 10.1017/s0960258500000283
|View full text |Cite
|
Sign up to set email alerts
|

Viable seeds buried in the tropical forest soils of Xishuangbanna, SW China

Abstract: This paper examines the composition and density of soil seed banks under a mature seasonal rain forest (>150 years old), three secondary forests (4 yr Trema orientalis forest, 9 yr Macaranga denticulata forest and 25 yr Mallotus paniculatus forest) and in a slash-and-burn field of Xishuangbanna, southwest China. Seeds in the secondary forests germinated most rapidly in the first week, while the seeds of the seasonal rain forest and the slash-and-burn field soils germinated slowly over the first 6 weeks and pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…For example, the notorious invasive species, Eupatorium adenophorum was the most abundant non-forest species both in soil seed banks and in understory vegetation in Lithocarpus xylocarpus forest edge zones. A native weed, Thysanolaena maxima, was the most dominant (relative abundance, 9.87%) species in soil seed banks in Shorea wantianshuea forest edge zones, and was also dominant in soil seed banks in a seasonal rainforest fragment interior (Cao et al, 2000). Although it was not found in understory vegetation, it could dominate secondary grasslands that developed on lands where most woody plants were removed by human activity (Zhang and Cao, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the notorious invasive species, Eupatorium adenophorum was the most abundant non-forest species both in soil seed banks and in understory vegetation in Lithocarpus xylocarpus forest edge zones. A native weed, Thysanolaena maxima, was the most dominant (relative abundance, 9.87%) species in soil seed banks in Shorea wantianshuea forest edge zones, and was also dominant in soil seed banks in a seasonal rainforest fragment interior (Cao et al, 2000). Although it was not found in understory vegetation, it could dominate secondary grasslands that developed on lands where most woody plants were removed by human activity (Zhang and Cao, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Trays were watered twice a day to keep the soil moist. Emerging seedlings were counted every 2 days for 6 months (see Cao et al, 2000), and those identified were removed with minimal disturbance to the soil. Seedlings that could not be identified were transplanted to pots at 6 months and grown to the flowering stage for identification to species.…”
Section: Sampling Soil Seed Banks and Seed Germinationmentioning
confidence: 99%
“…Moffatt and McLachlan (2003) reported that seeds of weedy and exotic species were positively associated with fragmentation, high levels of disturbance, and dry alkaline soils in riparian forests. Our previous study of the seasonal rain forest in Xishuangbanna, southwestern China, suggests that the high abundance of weeds in soil seed banks could be a result of local forest fragmentation and disturbance (Cao et al 2000;Tang et al 2006). Accordingly, we hypothesized that fragmentation of continuous forests significantly increases both richness and size of soil seed banks of nonconstituent species in the fragments.…”
Section: Introductionmentioning
confidence: 95%
“…Trays were watered twice a day to keep the soil moist. Emerging seedlings were counted every 2 days for 6 months (see Cao et al 2000), and those that were identified were removed with minimal disturbance to the soil. Seedlings that could not be identified were transplanted to pots and grown to the flowering stage for identification to species.…”
Section: Seed Germinationmentioning
confidence: 99%
“…Several studies suggested that burial may help to evade seed predation, either when burial occurs spontaneously (e.g., the seeds reach fi ssures in the soil or are covered by sediments after rainfalls) or when it is performed by animals (e.g., scatter-hoarding granivores). Nevertheless, most studies supporting these proposals were conducted in continuous forest ecosystems where seed predators can move freely across the landscape (e.g., Crawley and Long, 1995;Hulme and Borelli, 1999;Cao et al, 2000;Perea et al, 2012). Consequently, in these landscapes, seed consumers constantly move in search of those food resources that are easier to accede (e.g., seed exposed on the soil surface), while they ignore buried seeds because prey manipulation time (i.e., the time required to accede and consume a seed) is higher (Sork, 1983;Hulme and Borelli, 1999).…”
mentioning
confidence: 99%